Antioxidative and physiological responses of two sunflower (Helianthus annuus) cultivars under PEG-mediated drought stress - Baloglu, Mehmet Cengiz; Kavas, Musa; Aydin, Gulsum; Oktem, Huseyin Avni; Yucel, Ayse Meral (The Scientific and Technological Research Council of Turkey (TUBITAK-ULAKBIM) - DIGITAL COMMONS JOURNALS, 2012)
Drought stress is one of the most important yield-reducing factors in crop production. Sunflower, an oilseed crop, is severely affected by abiotic stress. In this study, 2 sunflower cultivars (Musala and Aydin) were evaluated in terms of various biochemical and physiological responses under 2 different polyethylene glycol-mediated drought stress conditions. Stress-determining parameters such as malondialdehyde (MDA), hydrogen peroxide (H2O2), and proline contents were determined. Both cultivars showed similar responses at osmotic potentials of both -0.4 and -0.8 MPa. Aydin was less affected than Musala under these stress conditions. MDA, H2O2, and proline levels were similar at both -0.4 and -0.8 MPa osmotic potentials in the 2 different cultivars. The 2 cultivars differed significantly in ascorbate peroxidase and catalase enzyme activities, which were more prominent in Aydin for both stress levels. However, glutathione reductase activity did not appear to be an essential part of the antioxidative system in either of the cultivars. Engineering antioxidative enzyme levels might provide a potential mechanism to cope with drought stress in sunflower.
Keywords: antioxidant enzymes; drought stress; Helianthus annuus; proline; 2. Zero hunger; 15. Life on land; 6. Clean water; 3. Good health